HUBUNGAN KARAKTERISTIK DENGAN PERIODE RAWAT INAP PASIEN COVID-19 YANG MENDAPAT TERAPI FAVIPIRAVIR - Endang Setyowati; Rika Muharyanti; Ari Simbara; Nura Ali Dahbul (IJF (Indonesia Jurnal Farmasi), 2022)
Background: Covid-19 is a disease caused by the SARS-CoV-2 (Server acute respiratory syndrome coronavirus 2) virus. The transmission of Covid-19 was so fast the on January 30, 2020 WHO declared Coronavirus as KKMD. The high number of cases of Covid-19 has resulted in a lack of capacity for health facilities, thus making inpatient medical services less than optimal and adequate.    Objective: To determine the relationship between characteristics with the period of hospitalization of Covid-19 patients receiving favipiravir therapy at the Mitra Bangsa Hospital, Pati.Methods: this type of analytic observational study with a retrospective approach, was conducted in May-June 2021 at Mitra Bangsa Hospital, Pati. Purposive sampling, and data collection using Covid-19 patient medical record. The number of sampels obtained was 59 respondents, and data analysis was carried out statistically using bivariat analysis with Chi Square test.Results: the most gender was male 32 patients (54.2%), the most age 46-59 as many 29 patients (49.2%), then Covid-19 patients had the most comorbidities as many as 39 patients (67.8%) with the most common disiase was diabetes melitus with 19 patiens (32.2%). The result of the Chi Square test showed that there was a relationship between gender with lengts of stay p-value: 0.640, relationship between age with length of stay p-value: 0.806, and comorbid relationship with length of stay p-value: 0.301.Conclusion: There is relationship between characteristics with the period of hospitalization of Covid-19 patients receiving favipiravir therapy at the Mitra Bangsa hospital Pati.Keywords: Covid-19, Favipiravir, Hospitalization